THE QUOTA RULE (AGE RESTRICTION) IN THE THIRD LEAGUE IN TERMS OF ACTORS (DRAMATIS PERSONAE) IN FOOTBALL - Mert Kerem Zelyurt; Muazzez Şaşmaz Ataçocuğu (ümit doğan üstün, 2017)
In 2016 it was seen that the "quota rule" (age restriction) which was put into practice in 2009 for the 3. League football teams in order to enable young players to have a better chance in squads and bring these players to the national teams have been changed because of not getting the desired results. In the study, the effects of 2009 quota rule which was established as a legal obligation to the football teams were examined in the extent of players, coaches, and the club managers (dramatis personae). The study was designed as "Semi-structured in-depth interview" (Qualitative Method) method. According to "Theoretical Sampling Method" the sample of the study was formed through 6 players, 4 club managers and 5 coaches all of which are active in the third football league. The interviews recorded in February 2017 and May 2017, which vary from 6 minutes to 29 minutes in length according to the samples, were converted into text and categorized under 4 themes in findings section. The themes are: 1. being dropped out of squad 2. Problems relating the squads and the quality of the football 3.The problem of player training in the third league for the national team and transfer mobility to upper leagues 4. The fall in wages, the problem of becoming unemployed and being obliged to play in the amateur football league. As it can be concluded from the themes which frame the narrations by the samples including different experiences considering their status and roles in terms of quota rule practice; some outcomes during the period in which the rule had been practiced (particularly due to the version before the change) were witnessed such as the deterioration in the quality of football, technical problems relating squads, the problem of vertical and horizontal professional mobility of the players and the fall in wages. In the last instance; it can be concluded that it is necessary to analyze legal sanctions relating a multivariate and intricate field such as football in terms of their possible multiple outcomes before putting them into practice. Considering this study, it is thought that analyzing the professional effects of legal changes to be made in order to regulate practices in football and other sports branches shall benefit both theoretically and for the sake of correct operation of the field of application.